Experimental and Numerical Study of Mechanical Properties of Concrete Containing Biochar - S.O Odeyemi; M.O Adisa; M.A Olawale; A.O Abdulsalam; J.A Oloba; H.A Ibrahim; B.O Sanusi; J.O Eda; F.O Obisiji (Journal of Building Materials and Structures)
The production of cement is responsible for 7% of worldwide CO2 emissions, leading to environmental threats and harm to ecosystems. Given the significant expenses involved and the necessity for substitutes such as biochar, there is a critical focus on investigating supplementary cementing materials (SCMs) to partially substitute traditional materials. The use of biochar as a concrete admixture is becoming more popular, and it has been investigated as a building material. Biochar is a solid organic residue produced by the pyrolysis of biomass. The experiment aimed to determine the mechanical characteristics of biochar-containing concrete using a concrete grade M20, cube moulds of dimension 100mm x 100mm x 100mm; cylinder moulds of 100mm x 200mm and beam formwork of dimension 150mm x 150mm x 1000mm were used to cast the control concrete sample and concrete containing varying percentages of biochar. Finite element analysis was also carried out using the ABAQUS program, utilizing concrete properties discovered through experimental study. The numerical and experimental study revealed that elevating the proportion of biochar in concrete led to about 17% decrease in compressive strength, 40% reduction in tensile strength, and about 25% reduction in the flexural strength of concrete beams. Both numerical and experimental approaches proved successful in assessing the influence of biochar on concrete.